2019
DOI: 10.20517/cdr.2019.46
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial determinants of chemoresistance

Abstract: Chemoresistance constitute nowadays the major contributor to therapy failure in most cancers. There are main factors that mitigate cell response to therapy, such as target organ, inherent sensitivity to the administered compound, its metabolism, drug efflux and influx or alterations on specific cellular targets, among others. We now know that intrinsic properties of cancer cells, including metabolic features, substantially contribute to chemoresistance. In fact, during the last years, numerous reports indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 138 publications
0
21
0
Order By: Relevance
“…Alteration of these genes are also associated to radioresistance through modulation of mitochondrial function. For example, PGC1α is a co-transcriptional regulation factor important in mitochondrial biogenesis, and upregulation of PGC1α has been linked to chemoresistance and altered energy metabolism in cancer stem cells [111 , 114] . PGC1α has been linked to radioresistance due to its role in the activation of many others transcription factors including nuclear respiratory factor 1 (NRF1) and 2 (NRF2) which, in turn, are linked to radiation response in cancer [115] .…”
Section: Genetic Regulation Of Mitochondria Energy Metabolism and Radmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of these genes are also associated to radioresistance through modulation of mitochondrial function. For example, PGC1α is a co-transcriptional regulation factor important in mitochondrial biogenesis, and upregulation of PGC1α has been linked to chemoresistance and altered energy metabolism in cancer stem cells [111 , 114] . PGC1α has been linked to radioresistance due to its role in the activation of many others transcription factors including nuclear respiratory factor 1 (NRF1) and 2 (NRF2) which, in turn, are linked to radiation response in cancer [115] .…”
Section: Genetic Regulation Of Mitochondria Energy Metabolism and Radmentioning
confidence: 99%
“…Studies investigating the role that bioenergetic drugs play in radiation response are increasing [136] . Metformin is a member of the biguanide class of drugs and is widely used as an antidiabetic drug worldwide to treat Type II diabetes [114] . Interestingly, several studies have shown that metformin might have a role as antineoplastic agent, and that metformin is linked to enhanced radiation response in cancer.…”
Section: Targeting Mitochondrial Energetics For Enhanced Radiosensitimentioning
confidence: 99%
“…Linking the intrinsic chemoresistance of CSCs to mitochondrial function is another emerging theme [25]. Interestingly, several previous works connect mitochondrial dynamics with chemoresistance in different cancer types [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mDivi-1 did not reverse the MCM-induced upregulation of EMT genes ( Figure 6C), suggesting that inhibition of mitochondrial fission does not interfere with the EMT genetic program per se, but rather impedes downstream cellular functions. Finally, considering the essential role of mitochondria in chemoresistance across different cancer types [25] and the intrinsic chemoresistance of CSCs, we studied the response to gemcitabine treatment in the context of mitochondrial fission inhibition. First, mDivi-1 treatment synergized with gemcitabine for inhibiting cell proliferation ( Figure 6D), an effect especially noticeable in PDX215 cells which were totally resistant to gemcitabine alone.…”
Section: Mdivi-1 Treatment Blocks Csc Functionalitymentioning
confidence: 99%
“…Interestingly, mDivi-1 did not reverse the MCM-induced upregulation of EMT genes ( Figure 6C), suggesting that inhibition of mitochondrial fission does not interfere with the EMT genetic program per se, but rather impedes downstream cellular functions. Finally, considering the essential role of mitochondria in chemoresistance across different cancer types [25] and the intrinsic chemoresistance of CSCs, we studied the response to Gemcitabine treatment in the context of mitochondrial fission inhibition. First, mDivi-1 treatment synergized with Gemcitabine for inhibiting cell proliferation ( Figure 6D), an effect especially noticeable in 215 cells which were totally resistant to Gemcitabine alone.…”
Section: Mdivi-1 Treatment Blocks Csc Functionalitymentioning
confidence: 99%